Microsoft Office FrontPage 2003, Illustrated Brief - Evans, Jessica (Cengage Learning, Inc, 2007)
Covers all the new features of Microsoft FrontPage 2003 such as "testing" Web designs, side-by-side coding and coding multiple Web browsers, the enhanced layout and graphics tools, and more! Students will learn basic to more advanced skills. A perforated FrontPage 2003 CourseCard back cover provides students a quick reference to FrontPage 2003 skills at their fingertips